Pressure-promoted irregular CoMoP2 nanoparticles activated by surface reconstruction for oxygen evolution reaction electrocatalysts. Issue 4 (7th January 2020) - Xu, Shishuai; Gao, Xiang; Deshmukh, Amol; Zhou, Junshuang; Chen, Ning; Peng, Wenfeng; Gong, Yutong; Yao, Zhiqiang; Finkelstein, Kenneth D.; Wan, Biao; Gao, Faming; Wang, Mingzhi; et al.
Abstract : Pressure-induced homogeneous CoMoP2 irregular nanoparticles, whose surface Co atoms form Co(OH)2 shells by reconstruction, and Mo atoms maintain the structural integrity. Abstract : Developing highly ordered and conductive phosphorous-based materials and identifying their active sites are critical to improve the catalytic performance for oxygen evolution reactions (OERs). Herein, we report a template-free and rapid high-pressure synthesis protocol to fabricate irregular CoMoP2 nanoparticles for OER catalysts. Pure CoMoP2 electrocatalysts show a reduced overpotential of 270 mV at 10 mA cm −2, improved kinetics and long-term stability. XAS, XPS and DFT calculations reveal that the reorganization induces highly active Co sites with a Co(OH)2 layer on the surface, while Mo atoms regulate electronic conductivity towards OER reduction potential and maintain the structural integrity of CoMoP2 . This work not only provides an identified activation mechanism for bimetallic catalysts, but also highlights the high-pressure synthesis as one of the alternative approaches for developing OER catalysts.